The Use of Sesame Oil Emulsion and Lemongrass Oil as Edible Coating Materials Against the Characteristics of Salak Gula Pasir Fruit (Zalacca Var. Amboinensis) during Storage - Simbolon, Ori Arauna; Pudja, Ida Ayu Rina Pratiwi; Aviantara, I Gusti Ngurah Apriadi (Jurnal BETA (Biosistem dan Teknik Pertanian), 2026)
Salak Gula Pasir (Zalacca Var. Amboinensis) is one of the leading salak varieties in Bali because it has a dominant sweet taste, no astringent taste, and high economic value in the market. Salak is an easily damaged fruit that causes a short shelf life due to various factors such as microbial contamination, respiration, and transpiration. Kind of the effort to inhibit the process is the application of edible coating. This study aims to the sesame oil and lemongrass oil effect as edible coatings with the best concentration of sesame oil and lemongrass oil on the characteristics of the fruit salak gula pasir during storage. The study used a complete randomized design (RAL) factorial with two factors. The first factor is sesame oil treatment on three concentration levels of 0%, 0.5%, and 1%. The second factor is the lemongrass oil emulsion treatment on four concentration levels of 0%, 0.5%, 1%, and 1.5%, and additional control treatment stored at room temperature 27 ± 3 °C. Every treatment was repeated three times, with a storage length of 10 days. The parameters observed in the study were: weight shrinking, vitamin C, total dissolved solids, and intensity of the damage. W1S1 treatment was the best combination with a weight shrinking value of 24.81%, vitamin C levels of 28.60 mg/100g, total dissolved solids of 20.15 0Brix, and damage intensity of 13.33%.